A Solution‐Processable Polymer‐Based Thin‐Film Thermoelectric Generator. Issue 1 (15th December 2020) - Kluge, Regina M.; Saxena, Nitin; Müller-Buschbaum, Peter
Abstract : Thermoelectric modules are capable of transforming thermal energy into electrical power. Implementing earth‐abundant and cost‐effective organic materials, they can contribute to an eco‐friendly way of energy production out of low‐grade waste heat and natural heat sources via the Seebeck effect. Moreover, the flexibility of organic materials can allow for adaption to curved surfaces such as the human skin and wearable electronics. Herein, a solution‐processable thermoelectric generator (TEG) using exclusively polymers as active materials is presented. The high‐mobility n‐type polymer poly[[ N, N ‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐ alt ‐5, 5‐(2, 2‐bithiophene)] (P(NDI2OD‐T2)) and the widely studied p‐type polymer blend poly(3, 4‐ethylene‐dioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) are combined into a thin‐film TEG. The presented device design is not limited to this system but is applicable to any pair of organic materials processable from solution and can be easily upscaled to fully flexible devices via, e.g., printing and roll‐to‐roll processing. Abstract : Thin‐film thermoelectric generators (TEGs) are wet‐chemically manufactured solely out of polymer materials forming the active layer in a new design approach in so‐called pseudo‐in‐plane geometry. The demonstrated power output, normalized per thermocouple, 1 K temperature difference, and 1 cm 2 active area of a single TEG leg is promising as compared to other organic TEGs.